Religiosity and attitudes towards professional mental health services: analysing religious coping as a mediator among Mexican origin Latinas/os in the southwest United States - Moreno, Oswaldo (Mental health, religion & culture, 2017)
In this study, we examined the relationship between religiosity and attitudes towards professional mental health services. We further examined whether internal religious coping and external religious coping mediated both relationships. Results indicated a significant association with religiosity and negative attitudes towards mental health services, as well as external religious coping and internal religious coping. Results also showed a nonsignificant association with both religious coping and negative attitudes towards mental health services. Finally, external religious coping mediated the relationship between religiosity and negative attitudes towards mental health services for men but not for women.